Veiled empire : gender & power in Stalinist Central Asia - Northrop, Douglas Taylor (EBSCO Academic Collection, 2004)
Drawing on research in Russian and Uzbekistani archives, the author reconstructs the turbulent history of a Soviet campaign that sought to end the seclusion of Muslim women. He shows it as emblematic of the larger Soviet attempt to bring the proletarian revolution to Muslim Central Asia.